2015
DOI: 10.3928/01913913-20150216-02
|View full text |Cite
|
Sign up to set email alerts
|

The Eagles Eye Mobile: Assessing Its Ability to Deliver Eye Care in a High-Risk Community

Abstract: Nurse training to reduce false-positive screening and strategies to improve attendance at arranged pediatric ophthalmologist consultations are recommended. The EEM effectively gets glasses to students where needed and use rates are satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Amongst the quantitative studies, increasing age was associated with lower spectacle wear in four studies [11][12][13][14] whereas in two studies, in India and the USA, younger children were less compliant. 15,16 A study in China of school children who reported already owning spectacles, also reported compliance to be lower in younger children [ .…”
Section: Agementioning
confidence: 97%
“…Amongst the quantitative studies, increasing age was associated with lower spectacle wear in four studies [11][12][13][14] whereas in two studies, in India and the USA, younger children were less compliant. 15,16 A study in China of school children who reported already owning spectacles, also reported compliance to be lower in younger children [ .…”
Section: Agementioning
confidence: 97%
“…For example, a study comparing a MHC in Baltimore with a comparable traditional clinic found that the percentage of clients who agreed to undergo human immunodeficiency virus (HIV) screening was higher at the MHC (54.4% in MHC vs. 7.1% in traditional clinic), and that the percentage of HIV tests that turned out positive was also higher at the MHC (5.4% in MHC vs. 2.0% in traditional clinic), indicating that MHCs facilitate more HIV screenings and are more efficient at reaching high-risk populations [ 58 ]. Because of their ability to connect with vulnerable individuals, MHCs can help identify additional cases of infectious and chronic diseases in a nontraditional setting [ 11 – 13 , 59 ].…”
Section: Improving Health Outcomesmentioning
confidence: 99%
“…Evidence indicates that MHC patients report an increased sense of self-confidence and ability to manage their chronic conditions and navigate the healthcare system [ 4 , 14 , 16 , 60 ]. One MHC in Pittsburg revealed that the trusting relationships clients fostered on the mobile clinic motivated patients to adopt healthier behaviors [ 11 ]. Furthermore, the HABITS for Life mobile screening program noted that 78% of its screening participants engaged in healthier behavior changes as a result of having participated in the screening [ 64 ].…”
Section: Improving Health Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Eagles Eye Mobile (EEM) offered treatment (prescribed spectacles) on the mobile unit itself . The study measured compliance of spectacle wear at 1, 4, and 12‐months post initial consultation.…”
Section: Discussionmentioning
confidence: 99%